LETTERING LITERATURE: FROM WRITING TO READING - Motta, Sergio Vicente [UNESP] (Univ Estado Mato Grosso, 2016)
The article discuss the concepts of lettering and literary lettering through the acting of two Guimaraes Rosa's characters, Grivo and Riobaldo. In the second part, it is brought the discussion to the fields of literary criticism and literary theory through texts by Antonio Candido, Roland Barthes, Denis Bertrand and Todorov.
Keywords: literary lettering; literature; reading; literary theory and criticism